2019
DOI: 10.1021/acs.jpcb.9b06958
|View full text |Cite
|
Sign up to set email alerts
|

Promotion Effect of Succinimide on Amyloid Fibrillation of Hen Egg-White Lysozyme

Abstract: Amyloid fibrillation is closely associated with a series of neurodegenerative diseases. According to that, the intermediate soluble oligomers and protofibrils are more toxic; reducing their concentrations in protein solutions by accelerating fibrillation is believed as a feasible strategy for treatment or remission of the diseases. Using hen egg-white lysozyme (HEWL) as a model protein, the promotion effect of succinimide was revealed by a series of experiments, e.g., atomic force microscopy (AFM), thioflavin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…In this study, the recyclability of the fabricated AgNsS2 is elucidated, making it a potential candidate from a cost-effective application point of view. Furthermore, the versatility of response was reviewed while acquiring surface enhanced Raman signal with the same recycled AgNS2 substrate with HEWL protein biomolecule that exhibited prominent Raman peak at 1655 cm −1 up to 50 nM trace, one of lowest reported in the literature of the alike analyte molecule [81][82][83]. Comparing the SERS research data available on HEWL, only this molecule was probed for SERS studies utilizing Horiba micro-Raman spectrometer (LabRAM HR Evolution), with 532 nm excitation, 50× objective, with 25% of total excitation power (~540 mW).…”
Section: Sensing Studies Using the Sersmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the recyclability of the fabricated AgNsS2 is elucidated, making it a potential candidate from a cost-effective application point of view. Furthermore, the versatility of response was reviewed while acquiring surface enhanced Raman signal with the same recycled AgNS2 substrate with HEWL protein biomolecule that exhibited prominent Raman peak at 1655 cm −1 up to 50 nM trace, one of lowest reported in the literature of the alike analyte molecule [81][82][83]. Comparing the SERS research data available on HEWL, only this molecule was probed for SERS studies utilizing Horiba micro-Raman spectrometer (LabRAM HR Evolution), with 532 nm excitation, 50× objective, with 25% of total excitation power (~540 mW).…”
Section: Sensing Studies Using the Sersmentioning
confidence: 99%
“…For the molecules of thiram, PA, MB we have obtained the highest EFs and smallest LODs among a horde of substrates [40][41][42][43][44][45][46][47][48][49]68,69,[79][80][81][82][83] investigated by our group in the last 10 years.…”
mentioning
confidence: 99%
“…Among them, succinimides are one of the important structural motifs with widespread biological and pharmaceutical activities 4 d – e as well as drug candidates. 5 For instance Liu et al (2019) reported the promotional effect of succinimide on amyloid fibrillation of HEWL (Hen Egg-White Lysozyme) 6 and several other reports also disclosed the use of succinimide derivatives as anticonvulsant drugs. 7 Although several routes have emerged for the synthesis of succinimide motifs, 8 the development of a new synthetic methodology which is much simpler than the existing ones is always an interesting area of research considering the various biological properties exhibited by succinimides.…”
Section: Introductionmentioning
confidence: 99%
“…The succimide motif is an intriguing member of N -containing heterocycles, pervasively presenced in natural active compounds, and a key reagent in synthetic chemistry . In addition, several succimide compounds have been used as medicine candidates for the promotion effect on amyloid fibrillation, treatment with neurodegenerative diseases, and anticonvulsant activity . Although a series of achievements were obtained, it still draws much attention to develop the concise and efficient stratagem for the construction of succimide scaffolds by employing readily available and inexpensive agents.…”
Section: Introductionmentioning
confidence: 99%